2011
DOI: 10.1080/1331677x.2011.11517441
|View full text |Cite
|
Sign up to set email alerts
|

Purchasing Power Parity In Mena Revisited: Empirical Evidence in the Presence of Endogenously Determined Break Points

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 176 publications
0
6
0
Order By: Relevance
“…Thorough investigation of the PPP dictum for the Middle East and North African countries is reported by Bahmani-Oskooee and Kandil (2007), and Kula et al (2011). In Bahmani-Oskooee and Kandil (2007), the real effective exchange rate series for 14 the Middle East and North African economies are evaluated with the KPSS test and the parity conditions are accepted in around half of the cases observed.…”
Section: Overview Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Thorough investigation of the PPP dictum for the Middle East and North African countries is reported by Bahmani-Oskooee and Kandil (2007), and Kula et al (2011). In Bahmani-Oskooee and Kandil (2007), the real effective exchange rate series for 14 the Middle East and North African economies are evaluated with the KPSS test and the parity conditions are accepted in around half of the cases observed.…”
Section: Overview Of Literaturementioning
confidence: 99%
“…The authors' estimations also show that in many of these countries nominal depreciation of exchange rates spills into real depreciation in the short-run as well as in the long-run. On the other hand, Kula et al (2011) apply the Lagrange Multiplier unit root test for official and black market exchange rates of 13 the Middle East and North African countries. After incorporating structural breaks in the data series from 1970 to 1998, the presence of mean reversion is established in 4 official exchange rates and in 5 black market exchange rates.…”
Section: Overview Of Literaturementioning
confidence: 99%
“…Voiena (2013); Biqing and Xiaowe (2012) and Rashid and Saedan (2013) on the other hand examined the impact of the 2008 financial crisis on the PPP. In addition to other studies that only conducted structural break tests without a pre specified interest on the driver of the break (For example, Kula et al (2011) reported evidence in favor of the PPP in the majority of countries as the deviations from the PPP were found finite.…”
mentioning
confidence: 99%
“…2 The degree to which mean reversion takes place is often measured by the half-life, a measure of the persistence of shocks, that indicates how long it takes for the impact of a unit shock to dissipate by half Kula, Aslan and Feridun (2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation